Faktor-Faktor Kesulitan Belajar Mata Pelajaran IPS Ekonomi Kelas XI di SMAN 2 Katingan Hilir - Tri Wahyudi; Santi Endriani (Neraca: Jurnal Pendidikan Ekonomi, 2017)
This study aims to determine the factors that cause learning difficulties of the XI-class Economics Social Sciences course at SMAN 2 Katingan Hilir. This study uses descriptive quantitative methods. The population in this study were all students of class XI IPS-1 and class XI IPS-2, which numbered 48 participants in the study. This study is a population study. the instruments used in this study were questionnaires. Based on the data the researchers collected was analyzed using a percentage formula. Based on the presentation of the data, it is obtained a general description of the factors of learning difficulties of Social Sciences Economics subjects in class XI at SMAN 2 Katingan Hilir namely internal factors, motivational indicators with a dominant category of 70.5%, attention indicators with less dominant categories of 42%, indicators interest with the dominant category is 62.5%, the memory indicator with the less dominant category is 44%.